(untitled) (Iranian Journal of Kidney Diseases, 2011)
ntroduction. Hepatitis B virus (HBV) infection is much more common in hemodialysis patients than the general population. Up to half of hemodialysis patients do not have adequate protective HBV antibodies after HBV vaccination. We studied the effects of adding levamisole, as an immunomodulator and adjuvant agent, on seroconversion response to HBV vaccination in hemodialysis patients. Materials and Methods. Thirty-six hemodialysis patients were divided into 2 groups. The first group received 40 microg of HBV vaccine intramuscularly at 0, 1, and 6 months plus 100 mg of oral levamisole per day for 12 days. The second group received the same amount and method of vaccine and placebo. Serum antibody levels were measured in each group after 0, 2, and 4 months after the last dose of vaccination. Results. Anti-HBV antibody level in the patients who received levamisole was lower than that in the control group. Antibody levels in the levamisole group at 0, 2, and 4 months after the last dose of vaccination were 44.4%, 77.8%, and 77.7%, respectively. In the control group, response rates at 0, 2, and 4 months were 55.6%, 72.2%, and 77.8% respectively (P = .04, P = .12, and P = .08, respectively). Conclusions. Anti-HBV antibody level was significantly lower immediately after HBV vaccination when it was accompanied by levamisole administration. However, no significant differences were observed between the two groups at 2 and 4 months. Further evaluation is recommended to assess the effect of adding levamisole on Hepatitis B surface antibody titer in hemodialysis patients.